Herpes simplex virus-1 infection or Simian virus 40-mediated immortalization of corneal cells causes permanent translocation of NLRP3 to the nuclei - Wang, Shu-Long; Zhao, Ge; Zhu, Wei; Dong, Xiao-Meng; Liu, Ting; Li, Yuan-Yuan; Song, Wen-Gang; Wang, Yi-Qiang (International journal of ophthalmology, 2015)
AIM: To investigate into the potential involvement of pyrin containing 3 gene(NLRP3), a member of the nucleotide-binding oligomerization domain-like receptors with cytosolic pattern recognition, in the host defense of corneas against viruses.METHODS: The herpes viral keratitis model was utilized in BALB/c mice with inoculation of herpes simplex virus-1(HSV-1). Corneal tissues removed during therapy of patients with viral keratitis as well as a Simian vacuolating virus 40(SV40)-immortalized human corneal epithelial cell line were also examined.Immunohistochemistry was used to detect NLRP3 in these subjects, focusing on their distribution in tissue or cells. Western blot was used to measure the level of NLRP3 and another two related molecules in NLPR3 inflammasome, namely caspase-1 and IL-1β.RESULTS: The NLRP3 activation induced by HSV-1infection in corneas was accompanied with redistribution of NLRP3 from the cytoplasm to the nucleus in both murine and human corneal epithelial cells. Furthermore,in the SV40-immortalized human corneal epithelial cells,NLRP3 was exclusively located in the nucleus, and treatment of the cells with high concentration of extracellular potassium(known as an inhibitor of NLRP3activation) effectively drove NLRP3 back to the cytoplasm as reflected by both immunohistochemistry and Western blot.· CONCLUSION: It is proposed that herpes virus infection activates and causes redistribution of NLRP3 to nuclei. Whether this NLRP3 translocation occurs with other viral infections and in other cell types merit further study.